Construction of a real vehicular delay-tolerant network testbed - Paula, Maicke Cabral Gomes de (2015)
Vehicular Delay-Tolerant Networks (VDTNs) appear as innovative network architecture, able to outline communication challenges caused by issues like variable delays, disruption and intermittent connectivity once that it utilizes the store-carry-and-forward method to allow that in-transit messages (called bundles) can be delivered to the destination by hopping over the mobile vehicles even that an end-to-end path does not exist. Since messages are stored persistently in a buffer and forward to the next hop, a new communication infrastructure is created allowing low-cost asynchronous opportunistic communication under the most critical situations like variable delays and bandwidth constraints. VDTN introduces a layered architecture, acting as an overlay network over the link layer, aggregating incoming IP packets in data bundles (large IP packets), using out-of-band signaling, based on the separation of the control plane and planes. This dissertation presents and evaluates the performance of a real VDTN testbed, demonstrating the real applicability of this new vehicular communication approach. It includes an embedded VDTN testbed created to evaluate safety systems in a real-world scenario. It was used cars with laptops to realize terminal and relay nodes. A real testbed is very important because some complex issues presented in vehicular communication systems can be treated with more realism in real-world environments than in a laboratory environment. The experiments were performed on the internal streets of Brazilian Fiat Automobile manufacturing plant. Performance measurements and analysis were also conduct to verify the efficiency of the system. The results obtained show that safety applications and services can be executed with the actual proposal VDTN architecture in several environments, although notable interference as fading and characteristics of the radio channel, require the use of more modern, appropriate and robust technologies. Thus, the real deployment of VDTNs confirms that VDTNs can be seen as a very promising technology for vehicular communications.